POSSIBILADES E ALTERNATIVAS Á CULTURA DO FUMO - Riffel, Cristiane Maria; Vela, Hugo; Souza, Marcelo Santos de; Souza, Roberto Martins de; Valdés, Juan Jose Guevara (Extensão Rural, 1998)
Disponivel em anexo.